Health Monitoring and Life on the Mississippi - Lynne S. Wilcox (Centers for Disease Control and Prevention, 2004)
Designing health monitoring systems is a complex task. This issue of Preventing Chronic Disease includes a report and commentary on measuring the burden of diabetes at the individual level in minority populations (1,2) and a report on measuring heart disease and stroke indicators at the policy level (3). To inspire stalwart professionals to design such systems, I turn to an individual recognized for his insightful commentary Mark Twain, also known as Samuel Clemens. Twain had a keen eye for the idiosyncrasies of human behavior, and his nonfiction works suggest he was adept at amateur qualitative research. Though he was a man of letters rather than a scientist, he clearly appreciated the issues involved in gathering quality information: There is something fascinating about science. One gets such wholesome returns of conjecture out of such a trifling investment of fact (4). The balance of conjecture and fact is a source of ongoing tension in public health: collecting data is time-consuming and costly, but operating health programs based on conjecture is risky.